Suitability of Leucaena leucocephala (Su-Babul) for Hard Boards - Shukla, K. S.; Shah, R. S.; Bagga, J. K. (Indian Forester, 1985)
Suitability or Leucaena leucocephala (Su-babul) bas been studied with a view of its utilisation in the manufacture of hard boards. Boards were prepared from pulp obtained after defiberating wood chips previously cooked in solution having varying concentration of Alkali(NaOH). It is observed that boards prepared from pulp obtained after cooking wood chips in 3 and 4 per cent alkali on the oven dry weight of chips have optimum strength values. Such boards after oil tempering treatment showed considerable improvements in the water resistance characteristics meeting the requirements of the Indian Specification IS: 1658-1977 for standard hard boards. Boards prepared with the same pulp using paraffin wax 2% on the weight of dry wood as sizing agent, also showed improvement in flexural strength and water resistance characteristic meeting the requirement of the above specification.